2003
DOI: 10.1074/jbc.m306230200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine String Protein (CSP) Inhibition of N-type Calcium Channels Is Blocked by Mutant Huntingtin

Abstract: Cysteine string protein (CSP), a 34-kDa molecular chaperone, is expressed on synaptic vesicles in neurons and on secretory vesicles in endocrine, neuroendocrine, and exocrine cells. CSP can be found in a complex with two other chaperones, the heat shock cognate protein Hsc70, and small glutamine-rich tetratricopeptide repeat domain protein (SGT). CSP function is vital in synaptic transmission; however, the precise nature of its role remains controversial. We have previously reported interactions of CSP with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…Various chaperones have been shown to interact and regulate the activity of ion channels of the plasma membrane [38,39]. Furthermore, chaperones have been shown to inhibit the activity of ion channels through a direct interaction or by interacting with intermediate partners [40,41]. In addition, stomatin, a homologue of SLP-2, is known to interact and negatively regulate mechanoreceptors, the ASIC3 channels in mammalian cells [17] and MEC4 in C. elegans [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Various chaperones have been shown to interact and regulate the activity of ion channels of the plasma membrane [38,39]. Furthermore, chaperones have been shown to inhibit the activity of ion channels through a direct interaction or by interacting with intermediate partners [40,41]. In addition, stomatin, a homologue of SLP-2, is known to interact and negatively regulate mechanoreceptors, the ASIC3 channels in mammalian cells [17] and MEC4 in C. elegans [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have yet enough elements to build up a mechanistic molecular model to explain the enhanced release in R6/1 synapses, it is likely that the upregulation of two SNARE proteins (synaptobrevins and SNAP-25) might be part of the molecular changes contributing to the gain of function phenotype in neurotransmitter release. On the other hand, CSP-␣, which has been shown to interact with mutant-htt (Miller et al, 2003), is required to maintain SNAP-25 levels (Chandra et al, 2005). Both proteins, CSP-␣ and SNAP-25, become reduced in Drosophila mutants lacking the palmitoyl transferase huntingtin-interacting protein 14 (Ohyama et al, 2007;Stowers and Isacoff, 2007).…”
Section: Increased Levels Of Synaptic Snares and Csp-␣ Interestinglymentioning
confidence: 99%
“…guanine nucleotide exchange factors (GEFs), 1 guanine nucleotide dissociation inhibitors, and GTPase-activating proteins). Our previous work has identified cysteine string protein (CSP) as a novel modulator of G proteins (1)(2)(3). Although the functional parallels between CSP and established G protein modulators are evident, the molecular mechanism by which CSP regulates G proteins is not yet known.…”
mentioning
confidence: 99%
“…We have shown that CSP associates with G proteins and promotes G␤␥ inhibition of N-type Ca 2ϩ channels (1)(2)(3). N-type Ca 2ϩ channels are effectors of G␤␥ such that direct binding of G protein ␤␥ subunits to the Ca 2ϩ channel ␣ 1 subunit results in a stabilization of the deep closed states of the channel (18).…”
mentioning
confidence: 99%